INVENTORY MANAGEMENT ECO- SYSTEMS AND WOMEN ENTREPRENEURS IN MICRO, SMALL AND MEDIUM ENTERPRISES IN JAMMU REGION, JAMMU AND KASHMIR, INDIA - Kour, Gurmeet; Yadav, Urmila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
An essential and vital component of a corporate enterprise's methodical supply chain strategy is inventory. By temporarily building up an excessive amount of inventory, the majority of micro and small businesses neglect inventory management (IM). The present study examines and evaluates the role of inventory management practices by women entrepreneurs in Micro Small and Medium Enterprises (MSMEs) in Jammu Region, India. Design/methodology/approach – The study is based on qualitative and behavioral case study design. Data were gathered from 15 MSMEs owners in Jammu region. The study used purposive sampling technique with semi-structured interview to gathered information data. The NVivo software technique is used to evaluate and analyze the data. Findings – The finding of study indicate most MSMEs enterprises owners purchase their raw materials from local market with local sources; however few of them purchased their raw materials from boundaries states. They frequently adopt technologies and online media platform to manage raw materials and make payment through online method. Additionally, the survey found that MSMEs' owners are unable to purchase large quantities of raw materials because of their limited financial resources, waste, and damage, with a leading ratio of 12–15%. Research limitations/implications – The research will positively contributes to MSMEs associations, trade association, and government to concern over inventory management. The study recommends reducing tax burden to improve to buying MSMEs raw materials and inventories and reduce taxes to promote exporting of the product. Value/Originality – This is the primary study that focuses on the IM systems among women entrepreneurs of MSMEs in Jammu region, India.